2011
DOI: 10.1088/0004-637x/732/2/61
|View full text |Cite
|
Sign up to set email alerts
|

The Tucana/Horologium, Columba, Ab Doradus, and Argus Associations: New Members and Dusty Debris Disks

Abstract: We propose 35 star systems within ∼70 pc of Earth as newly identified members of nearby young stellar kinematic groups; these identifications include the first A-and late-B type members of the AB Doradus moving group and field Argus Association. All but one of the 35 systems contain a bright solar-or earlier-type star that should make an excellent target for the next generation of adaptive optics (AO) imaging systems on large telescopes. AO imaging has revealed four massive planets in orbit around the λ Boo st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
288
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(298 citation statements)
references
References 67 publications
7
288
2
1
Order By: Relevance
“…Additional evidence for a young age of the Columba association comes from the interferometric measurements of the proposed member HR 8799 (Zuckerman et al 2011), where the radius of the star is consistent with an age ∼30 Myr (Baines et al 2012) 9 . Dynamical stability studies of the planetary system that orbits HR 8799 provide additional indirect evidence for a young system age.…”
Section: Tucana Columba Carina and Argusmentioning
confidence: 93%
“…Additional evidence for a young age of the Columba association comes from the interferometric measurements of the proposed member HR 8799 (Zuckerman et al 2011), where the radius of the star is consistent with an age ∼30 Myr (Baines et al 2012) 9 . Dynamical stability studies of the planetary system that orbits HR 8799 provide additional indirect evidence for a young system age.…”
Section: Tucana Columba Carina and Argusmentioning
confidence: 93%
“…van Leeuwen (2007) reported a Hipparcos parallax of 20.31 mas, placing it at a distance of r ≈ 49 pc. McDonald et al (2012) reported an effective temperature of T eff ≈ 6032 K, while the estimate of Vican & Schneider (2014) was T eff ≈ 6100 K. Furthermore, Vican & Schneider (2014) reported a radius of R ≈ 1.05 R , while Zuckerman et al (2011) presented the value R ≈ 1.08 R . We adopted the value 1.1 R .…”
Section: V1358 Orimentioning
confidence: 93%
“…Montes et al 2001), while HD 29615 has been proposed as a member of the Tucana/Horologium association indicating an age of ∼30 Myr (see e.g. Zuckerman et al 2011). They are, however, slightly hotter than the young Sun.…”
Section: Observed Stars and Their Adopted Stellar Parametersmentioning
confidence: 99%
“…Therefore, for a given detection threshold, observing younger stars is sensitive to lower mass planets. Our sample selection is based on recent publications on associations (AB Dor, β Pic, Her/Lyr, Argus, Tuc/Hor, Columba, and Upper Cen/Lupus) from Zuckerman et al (2011), Torres et al (2008 and Rhee et al (2007). Indeed, stars belonging to these moving groups share common kinematic properties and ages.…”
Section: Target Selectionmentioning
confidence: 99%
“…HIP 114189 / HR 8799 -HR 8799 is a well-known λ Boo, γ Dor star, surrounded by a debris disk ) and belonging to the 30 Myr-old Columba association (Zuckerman et al 2011). It hosts four planetary-mass companions between 14 and 68 AU (Marois et al 2008(Marois et al , 2010, which makes this multiple-planet system the first imaged so far.…”
Section: Substellar Companionsmentioning
confidence: 99%